2022
DOI: 10.1177/17479541221122411
|View full text |Cite
|
Sign up to set email alerts
|

Coach competence, justice, and authentic leadership: An athlete satisfaction model

Abstract: This study analyzed the relationship between athletes' perception of coach competence and their satisfaction, mediated by the influence of authentic leadership and perceived justice in team sports players. A cross-sectional study carried out with 115 (49.6% women and 50.4% men; 17.96 ± 2.85 years old; 8.18 ± 4.67 years of experience), soccer (53.9%), and handball (46.1%) players, all members of performance teams. The player's perception of coach competency, authentic leadership, justice, and satisfaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The results confirmed that the scale could be used as a valuable tool in examining the construct of AJ. Since athletes' perceived fairness toward coaches' decisions and behaviors could build a strong relationship between coaches and athletes [ 6 , 58 , 59 ], future studies could use this tool to extend relevant research by examining the relationships between each dimension and various outcomes, such as quality of relationship between athletes and coaches, team cohesion and commitment, athletes' citizenship behaviors, and individual/team performance. In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that the scale could be used as a valuable tool in examining the construct of AJ. Since athletes' perceived fairness toward coaches' decisions and behaviors could build a strong relationship between coaches and athletes [ 6 , 58 , 59 ], future studies could use this tool to extend relevant research by examining the relationships between each dimension and various outcomes, such as quality of relationship between athletes and coaches, team cohesion and commitment, athletes' citizenship behaviors, and individual/team performance. In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ]. Based on the findings of relevant research regarding the athlete-coach relationship [ [58] , [59] , [60] ], the conceptual framework (as shown in Fig. 2 ) can be developed to describe the relationship between AJ and potential outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to SDT's explanation of the satisfaction of basic psychological needs, the coaching role and its competence exerts a significant influence on athletes' motivation and performance through various mechanisms (Xitao et al, 2021). The way athletes perceive their coaches' behavior and ability to coach them plays a fundamental role in the relationship between the two (Soto-García et al, 2023). In this sense, it is common for coaches to priorities knowledge and ability to coach athletes over other psychosocial variables such as leadership or justice, nevertheless, recent evidence supports the relevance of prior the attention on these variables into the sports context (Bosselut et al, 2018;De Backer et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…In the middle of the space between these two variables, many other factors affect coach-athlete interaction, as well as sport performance and athlete satisfaction. In response, some authors have investigated the role of psychosocial elements such as leadership or fairness in athletes' perceptions of coaches (Bosselut et al, 2012;De Backer et al, 2011;Leo et al, 2019;Pires et al, 2022;Soto-Garcia et al, 2021, 2023. Leadership in sport is described as a process which the coach, manager or even the same athletes can influence the motivation and behavior of the others (athletes/teammates) to look for and work for achieve a common goal (Turnnidge & Côté, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation